The Reconstruction of Various Complex Full-Thickness Skin Defects with a Biodegradable Temporising Matrix: A Case Series - Julie van Durme; Thibaut Dhont; Ignace De Decker; Michiel Van Waeyenberghe; Kimberly De Mey; Henk Hoeksema; Jozef Verbelen; Petra De Coninck; Nathalie A. Roche; Phillip Blondeel; Stan Monstrey; Karel E. Y. Claes (European Burn Journal)
Background and Objectives: Traditionally, full-thickness skin defects (FTSDs) are covered with split-thickness skin grafts (STSGs). This usually provides an epidermal coverage but entails a high risk of hypertrophic scarring mainly due to the absence of the dermal layer. The Novosorb® Biodegradable Temporising Matrix (BTM) is a novel synthetic dermal substitute that has been used for the reconstruction of various complex and/or large defects in our center. The aim of this article is to evaluate the clinical performance of the BTM as a synthetic dermal substitute for complex FTSD reconstruction in a European context. Materials and methods: This case series focused on the treatment of complex FTSDs with the BTM. After wound debridement, the BTM was applied according to a defined protocol. Once adequate vascularization was observed, the sealing membrane was removed and the neo-dermis was covered with STSGs. Patient demographics, comorbidities, wound defect localization and etiology, wound bed preparations, time of BTM application and removal, time to complete wound healing after STSG, complications, and HTS formation were recorded. Results: The BTM was used to treat FTSDs in six patients with complex wounds from degloving (3), burns (1), ulcerations (1), and necrotizing fasciitis (1). Successful integration occurred in five cases (83%), with one partial integration. The BTM remained in situ for an average of 20.7 days before delamination and STSG coverage. No major complications occurred, though one case had hypergranulation with secondary STSG infection. Two patients were lost to follow-up, while the remaining four had excellent aesthetic and functional outcomes with good-quality scars. Conclusions: Within the limits of this small and heterogeneous case series, the BTM appears to be a promising option for the reconstruction of complex FTSDs of varying etiologies. Its successful integration in most cases and limited complication rate support its clinical potential. However, given this study’s retrospective design and limited sample size, further prospective studies are required to validate these findings and assess long-term outcomes.